2017
DOI: 10.1080/03639045.2017.1391836
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of nutraceutical coenzyme Q10 nanoemulsion with improved skin permeability and anti-wrinkle efficiency

Abstract: Coenzyme Q10 (CoQ10) is an insoluble, poorly permeable antioxidant with great biological value which acts as anti-aging and anti-wrinkle agent. To improve its permeability through topical application, the current study aimed at formulating oil/water (o/w) nanoemulsion (NE) as an efficient vehicle for delivering (CoQ10) through the skin barriers. The solubility of (CoQ10) was tested for various oils, surfactants (S), and co-surfactants (CoS). The NE region was determined by constructing pseudoternary phase diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 40 publications
0
37
0
1
Order By: Relevance
“…However, the SMEDDS still showed a low solubility of CoQ10 [37]. A nanoemulsion containing CoQ10 using Tween 80 was developed for alleviating the formation of wrinkles [38]. Another study reported that a CoQ10 microemulsion using glycosphingolipids demonstrated high CoQ10 solubility and improved bioavailability when orally administered, with CoQ10 used as a food ingredient and not a therapeutic agent [39].…”
Section: Discussionmentioning
confidence: 99%
“…However, the SMEDDS still showed a low solubility of CoQ10 [37]. A nanoemulsion containing CoQ10 using Tween 80 was developed for alleviating the formation of wrinkles [38]. Another study reported that a CoQ10 microemulsion using glycosphingolipids demonstrated high CoQ10 solubility and improved bioavailability when orally administered, with CoQ10 used as a food ingredient and not a therapeutic agent [39].…”
Section: Discussionmentioning
confidence: 99%
“…Thus it may be beneficial to protect cells from reactive oxygen species-induced damage through improving local antioxidant activity in wounds (10). It is known that several numerous markers such as matrix metalloproteinases, SOD-1, CAT, reduced (11)(12)(13). In vitro models for studies investigating experimental burn injuries are limited.…”
Section: Discussionmentioning
confidence: 99%
“…In this area, a pre-existing—and current—literature has focused on the role of mitochondria in creating a prooxidant state since the early studies [ 78 , 79 ]. Hence, a line of studies has pursued MN-containing preparations [ 80 , 81 ], and a body of literature has reported the favorable effects of topical MN administration using ALA [ 82 , 83 ] or CoQ10 [ 84 , 85 ] or CARN [ 86 ], as evaluated in clinical trials. In several studies, MN administration was accompanied by other ingredients.…”
Section: Mitochondrial Nutrient-based Clinical Trials In Aging-relmentioning
confidence: 99%